Operation theatre time utilization during emergency surgeries at a government institute of trauma in Karachi, Pakistan - Rabia Asim; Humera Ismail; Shehla Baqi (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate operation theatre time utilisation during emergency cases. Method: The prospective, observational study was conducted at the Shaheed Mohtarma Benazir Bhutto Institute of Trauma, Karachi, from January 17 to April 17, 2020, during which the three dedicated emergency operating rooms at the centre were monitored for time from transferring the patient to the operation theatre till the patient was is shifted out after surgery. Data was analysed using SPSS 24. Results: Of the total 1,287 surgeries performed, 625(48.56%) were included. Of them, 373(59.7%) patients were shifted to the operation theatre once it was ready, while 252(40.3%) were shifted in advance. There were 474(75.8%) male patients, and 151(24.1%) were females. The overall mean age was 32.7±17.4 years (range: 1 year to 47 years). Mean time of patient transfer to the operating room was 1:17±1:52 hours:minutes. Delay was recorded in 133(35. 6%) cases who were shifted from location when the operation theatre was available. It was caused in 64(17.15%) cases by surgical teams, another emergency surgery in the operating room 24(6.4%) and operating room cleaning 19(5%). The mean waiting time in the holding area was 1:25±1:21hours:minutes, and mean time from induction to surgical incision was 0:34±0:32 hours:minutes. Delays was caused by trainee surgeons in 79(12.64%) cases, and prolonged preoperative patient preparation in 99(15.84%). Mean turnover time was 0:48±0:42 hours:minutes. Delay was caused by post-operative unavailability of ambulance transportation 29(15%), and intensive care unit bed availability 14(7.2%). Conclusion: Time utilisation of emergency operation theatres can be maximised by improved overall coordination. Key Words: Government institute, Emergency, Operation theatre, Time sationutilisation.